Impoliteness on Twitter by Malaysians - Pung, Wun Chiew; Siti Nur Amira, Mohd Faizal (UNIMAS Publisher, 2023)
This study investigates impoliteness on Twitter in the context of Malaysian users. The objectives of the study are to examine the impoliteness strategies and triggers of impoliteness found in tweet replies on tweets on issues related to COVID-19. The data consist of 440 tweet replies on COVID-19, posted from May 2020 to May 2021 which contain elements of impoliteness. The study uses Culpeper’s (2005) impoliteness model and Culpeper’s (2011) framework for examining impoliteness triggers. The findings show that four types of impoliteness strategies are used in the tweet replies: bald-on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock impoliteness. The most dominant type of impoliteness strategy is positive impoliteness, while bald-on record impoliteness is the least employed impoliteness strategy. Pointed criticism is found to be the most often occurring impoliteness trigger in the study, followed by insult, negative expressive, and challenging or unpalatable question and/or presupposition. The findings suggest culture and the communication platform may play a role in the use of impoliteness strategies and impoliteness triggers in the tweets.